Dynamic signal analyses in dry sliding wear tests - Bergantin,R. (2003)
This work proposes to perform a dynamic analysis of the friction force and the vibrations produced in pin-on-disk sliding tests. The sliding tests were run under dry condition with austenitic stainless steel and high-speed steel pairs. The obtained results were the pin mass loss, the average friction force and power spectrum density (PSD) graphs of the friction force and vibrations in normal and tangential directions to the contact. It was possible to notice that some natural frequencies of the machine system are excited during the tests. Analyses of the magnitudes of a specific frequency could show the existence of a relation between the machine system dynamics and the average friction and wear results, and it depended on the tested materials.